An economic value of the glycated hemoglobin test in diabetes mellitus type 2 diagnosis - Marina V. Shestakova (Endocrinology Research Centre, 2019)
BACKGROUND: Diagnostic of diabetes mellitus type 2 (DM2T) in time is very actual for treatment and prevention of potential complications of illness. Fasting blood glucose test (FBG) is a widely used method of primary DM2T diagnose. Glycated hemoglobin (HbA1c) test is an alternative and used more rarely due to expensive. AIM: Modelling of comparative expenditures for DM2T control in cases of primary diagnostic by HbA1c test or FBG test usage in 20-years horizon. METHODS: Retrospective analysis of aggregated epidemiological Russian NATION study data in 810 patients with prediabetes and DM2T with both analysis performed, with sensitivity and specificity of each is detected. The simulation model of DM2T outcomes has been used for Health Technology assessment (direct and indirect costs of Diabetes control during 20 years). Three algorithms of the DM2T treatment were investigated for understanding of expenditures in case on diagnostic on-time and case of late verification with metformin, gliflozines, gliptins, Glucagon-like peptide-1 receptor agonists, basal insulin analogs and their combinations. RESULTS: FBG test has more negative results for DM2T diagnostics in compare with HbA1c analysis (77,4% and 36,5% accordingly). Amount of false negative results in FBG test in 3 times more often occurred in comparison with HbA1c. HbA1c test in 3 times more precisely than FBG test for carbon metabolism abnormalities detection. Diagnostic in time with HbA1c test in compare with late process of illness detection by FBG can cut common expenditures on 26,3-27,7% depending on treatment option due to macrovasular complications decreasing. Disability rate is expected decrease on 21% to 20-th year in case of diagnostic with HbA1c performing instead FBG test. CONCLUSION: HbA1c test has diagnostic advantages in compare with FBG test for primary investigation (dispanserization). Direct and indirect expenditures in average for one patient with DM2T on 20-years horizon including cost of drugs, analysis, complications, disabilities are less in case of diagnostic in time with HbA1c test in comparison with late diagnostics in case of FBG test execution.